A Study on the learning Styles of Nursing and Midwifery Students in Yasuj According to the VARK Model (2013) - M Behnam Moghadam; A Behnam Moghadam; A Rostaminejad; T Salehian (Armaghane Danesh Bimonthly Journal, 2015)
Background & aim: learning style(s) is one of the factors effective learning. Information about students learning styles can aid the presentation of teaching appropriate to their individual style. The purpose of this study was to determine the learning styles of Yasuj nursing and midwifery students based on the VARK model in 2013.